Validation of microsatellite loci for Balfourodendron riedelianum through analysis of Mendelian inheritance, genetic linkage, and genotypic linkage disequilibrium - Aguiar, B.; Gandara, F. B.; Freitas, M. L. M.; Moraes, M. L. T. [UNESP]; Kageyama, P. Y.; Sebbenn, A. M. (Sciendo, 2019)
Balfourodendron riedelianum is a tropical tree endemic to the Atlantic Forest biome that is currently endangered due to forest fragmentation and extensive exploitation. Three populations of the species are conserved ex situ in a provenance and progeny test at the Luiz Antonio Experimental Station, Sao Paulo State, Brazil. To verify if seven microsatellite loci developed for the species can be used as genetic markers in analyses focused on conservation and sustainable use strategies, leaf tissue samples were collected from the three provenances and from 17 seed trees in one provenance. We analyzed Mendelian inheritance and genetic linkage for the 17 seed trees and genotypic linkage disequilibrium for individuals from the three provenances. For six of the seven loci analyzed, all 17 seed trees showed heterozygosity. The inheritance and genetic linkage analyses were performed using respective locus, while the genotypic linkage disequilibrium analysis was performed for the seven loci. After Bonferroni correction, none of the 75 tests showed deviation from Mendelian segregation and genetic linkage, nor did we detect genotypic linkage disequilibrium. The results suggest that six of the seven loci can be used for population genetics studies on B. riedelianum.
Keywords: Atlantic Forest; Conservation genetics; Inheritance; Microsatellite markers; Tropical tree species